Liver transplant after donation from controlled circulatory death versus brain death: A UNOS database analysis and publication bias adjusted meta‐analysis. Issue 2 (30th October 2021) - Ziogas, Ioannis A.; Kakos, Christos D.; Esagian, Stepan M.; Skarentzos, Konstantinos; Alexopoulos, Sophoclis P.; Shingina, Alexandra; Montenovo, Martin I.
Abstract: Background: Donation after circulatory death (DCD) is an increasingly utilized alternative to donation after brain death (DBD) to expand the liver donor pool. We compared the outcomes of liver transplant (LT) after DCD versus DBD. Methods: A PRISMA‐compliant systematic literature review was performed using the PubMed, Cochrane Library, and Embase databases (end‐of‐search‐date: July 2, 2020). US outcomes were analyzed using the UNOS database (February, 2002–September, 2020). Pooled hazard ratios (HR) for patient and graft survival were obtained through random effect meta‐analyses and adjusted for publication bias. Results: Thirteen studies reporting on 1426 DCD and 5385 DBD LT recipients were included. 5620 DCD and 87561 DBD LT recipients were analyzed from the UNOS database. Meta‐analysis showed increased risk of patient mortality for DCD (HR = 1.36; 95%CI, 1.09–1.70; P  = .01; I 2  = 53.6%). When adjusted for publication bias, meta‐analysis showed no difference in patient survival between DCD and DBD (HR = 1.15; 95%CI, .91–1.45; P  = .25; I 2  = 61.5%). Meta‐analysis showed increased risk of graft loss for DCD (HR = 1.50; 95%CI, 1.20–1.88; P  < .001; I 2  = 67.8%). When adjusted for publication bias, meta‐analysis showed a reduction in effect size (HR = 1.36; 95%CI, 1.06–1.74; P  = .02; I 2  = 73.5%). Conclusion: When adjusted for publication bias, no difference was identified between DCD and DBD regarding patient survival, while DCD was associated with an increased risk of graft loss.